Impact of Typhoon Kalmaegi (2014) on the South China Sea: Simulations using a fully coupled atmosphere-ocean-wave model. (November 2018) - Wu, Renhao; Zhang, Han; Chen, Dake; Li, Chunyan; Lin, Jianmin
Highlights: A fully coupled atmosphere-ocean-wave model is designed to study the impacts of Typhoon Kalmaegi on the South China Sea. The model results are consistent with observations. The air-sea thermal and dynamic responses are discussed in detail. The along-track internal wave response and its interaction with topography are revealed. The most significant cooling is found over the slope region, and its relevant mechanisms are given. Abstract: A fully coupled atmosphere-ocean-wave model is applied to study the upper ocean response of the South China Sea (SCS) to Typhoon Kalmaegi. The model results are validated by satellite observations and in situ observations at four stations. The coupled model system reproduces the air-sea thermal and dynamic features. Typhoon Kalmaegi passed through the SCS with a mean translation speed of approximately 8.0 m s −1, a fast-moving storm with a predominantly baroclinic ocean response. The results show some typhoon-induced rightward intensifications in sea surface cooling, current speed, and significant wave height. They also show inertial pumping with alternating upwelling and downwelling, and strong isotherm and current oscillations with near-inertial frequencies. Some remarkable ocean responses are also found: (1) a significant cooling occurred in the northern SCS slope and shelf regions; and (2) the storm induced a near-inertial internal wave propagating in the track direction, where the wave crest impinged the slope and climbed up the shelf. A two-layer ocean current response and strong mixing at the slope bottom induced by breaking waves are also observed. A heat budget analysis shows that the vertical diffusion dominates the rate of change of temperature in the upper layer, while the total advection plays a major role in the subsurface layer. The net surface heat flux makes a minor contribution to cooling in the upper layer on the right side of the storm's track. In contrast, its contribution to the surface layer cooling on the left side is comparable to that of the vertical diffusion terms, indicating that surface heat fluxes cannot be ignored in this region.